2011
DOI: 10.1590/s0102-79722011000300016
|View full text |Cite
|
Sign up to set email alerts
|

Italian students' social representation on aging: an exploratory study of a representational system

Abstract: In various countries there are studies aimed at characterizing social representations on aging, but little is known about their relations with other representations. The present study proposes to characterize those relations through the notion of representational systems. An exploratory survey has been conducted with 151 Italian undergraduate students. They have completed evocation tasks about seven social objects linked to aging and also rated the distances among them. Distance ratings went through similarity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
5

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 15 publications
(13 reference statements)
0
4
0
5
Order By: Relevance
“…They have important influences on behavior and operate through a variety of mechanisms (Helmes & Pachana, 2016). Stereotypes of aging include assumptions and generalizations about older people without regard for individual differences or unique circumstances (Fiske & Tablante, 2015;Moreira, 2012;Wachelke & Contarello, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…They have important influences on behavior and operate through a variety of mechanisms (Helmes & Pachana, 2016). Stereotypes of aging include assumptions and generalizations about older people without regard for individual differences or unique circumstances (Fiske & Tablante, 2015;Moreira, 2012;Wachelke & Contarello, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…A study carried out with young Italian students concerning the social representation of the aging process observed that the characterization of the aging process may be grounded on the mutual connection and dependence among social objects, such as health, family, body, work, time and death. The family is pointed out as a fundamental social unit, as it is usually referred to as the element in which people look for support (12) . In the old age, we need to count on a strong emotional support that enables us to accept and adapt to eventual losses and limitations in a better way (5) .…”
Section: Discussionmentioning
confidence: 99%
“…Em relação aos trabalhos supracitados (Camargo & Wachelke, 2010;Wachelke & Contarello, 2011;e Wachelke, 2012), vale ressaltar a pertinente revisão de literatura que os autores apresentaram acerca do conceito de sistema representacional. Tal revisão se mostrou relevante ao ponto que foi incorporada à introdução deste artigo.…”
Section: Srs Como Conjunto De Representações Sociaisunclassified
“…Nas palavras de Wachelke (2005): "O que propomos é considerar que nenhum dos dois sistemas representacionais (ciência e tradição cultural) oferece possibilidade de explicar satisfatoriamente a loucura, enquanto objeto da sociedade" (p. 316). Vale ressaltar que, nessa publicação, o autor trabalha com um conceito distinto daquele apontado em obras mais recentes (Carmargo & Wachelke, 2010;Wachelke & Contarello, 2011;Wachelke, 2012).…”
Section: Srs Como Conjunto De Conhecimentosunclassified